2008
DOI: 10.1021/jp805210v
|View full text |Cite
|
Sign up to set email alerts
|

Equilibria of 3-Pyridylmethanol with Copper(II). A Comparative Electron Spin Resonance Study by the Decomposition of Spectra in Liquid and Frozen Solutions

Abstract: The copper(II)-3-pyridylmethanol (L) system was investigated in aqueous solution by two-dimensional ESR evaluation at 298 K, and computer simulation of the individual anisotropic spectra at 77 K. The data revealed that the paramagnetic copper(II) complexes [CuL] (2+), [CuL 2] (2+), [CuL 3] (2+), and [CuL 4] (2+) are formed up to pH approximately 7 at a moderate or high excess of ligand. As compared with chelating ligands, two differences were observed for the complexation of 3-pyridylmethanol with copper(II): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Under the conditions mentioned above, a g-value of 2.212 was found for Cu 2+ which is comparable to those reported for other copper(II) compounds in solution at room temperature. 22 Thus, we confirmed that the final product is Cu 2+ in solution.…”
Section: Paper Dalton Transactionssupporting
confidence: 70%
“…Under the conditions mentioned above, a g-value of 2.212 was found for Cu 2+ which is comparable to those reported for other copper(II) compounds in solution at room temperature. 22 Thus, we confirmed that the final product is Cu 2+ in solution.…”
Section: Paper Dalton Transactionssupporting
confidence: 70%
“…It shall however be mentioned, that the EPR spectra were recorded in frozen solutions, where the change of the chemical equilibria cannot be avoided. 43 At metal excess, two dinuclear complexes are the major species in the system (Fig. 2a, dashed lines).…”
Section: Cu(ii) Complexes Of (Gh) 2 Kmentioning
confidence: 97%